The First Cat in Space and the Wrath of the Paperclip - Book 3 - Barnett, Mac; Harris, Shawn (Artist) (New York, NY : HarperAlley, an imprint of HarperCollinsPublishers, 2024)
"4.5 billion years ago . . . an AI paperclip named CheckMate was designed to fix grammatical errors. Exhausted of correcting "who" vs. "whom," it concocted a plan to eliminate spelling errors once and for all. All life-forms would be turned into something beautiful, practical, perfect: a paperclip. Thankfully, it was buried in the debris. Long forgotten . . . until it was accidentally freed. Now CheckMate has invaded every computer on Earth and is bent on fulfilling its dastardly plot. There's only one trio who can save the day: the First Cat in Space, the Moon Queen, and LOZ 4000. But when CheckMate zoops First Cat's spacesuit, our titular hero is now powerless. The fate of the world depends on...a regular little kitty cat. Will everyone in the universe become school supplies?!"--
Keywords: Cats -- Comic books, strips, etc; Robots -- Comic books, strips, etc; Space flight -- Comic books, strips, etc; Paper clips -- Comic books, strips, etc; Artificial intelligence -- Comic books, strips, etc; Good and evil -- Comic books, strips, etc; Comic books, strips, etc. -- United States; Cats -- Fiction; Robots -- Fiction; Space flight -- Fiction; Paper clips -- Fiction; Artificial intelligence -- Fiction; Good and evil -- Fiction; Cartoons and comics; Graphic novel; Funny animal comics; Science fiction comics; Humorous comics; Comics (Graphic works); Graphic novels